Comparative study between proximal femoral nailing versus dynamic hip screw in unstable inter-trochanteric fractures of the femur in adults - Kumar, Manoj; Lone, Zubair A.; Bhatt, M. Farooq; Basit, Abdul (International Journal of Research in Medical Sciences, 2021)
Background: Hip fractures are more common in elderly among them intertrochanteric fractures are most common, more than 50% fractures are unstable. The proximal femoral nailing (PFN) and dynamic hip screw (DHS) are frequently used modalities from last two decades in both stable and unstable fractures. The DHS has been shown to produce good results but complications are frequent, particularly in unstable inter-trochanteric fracture. The advantage of PFN fixation is that it provides a more biomechanically stable construct with good collapse control. The goal of this study was to compare the clinical and radiographical results of the DHS and PFN for the treatment of inter-trochanteric hip fractures as one is load bearing another is load shearing. Methods: In our study we included 70 inter-trochanteric fractures, out of which 40 were treated with DHS fixation and 30 were treated with PFN, and were followed up at regular intervals of 2 weeks, 8 weeks, 12 weeks, 6 months and annually thereafter. Results: The functional results were assessed with Harris hip score and observed 35% excellent results in DHS group and 63.3% excellent results in PFN group. We observed no statistically significant difference between two groups in view of late and early complications and time to union. We observed significantly better outcomes in PFN group for unstable inter-trochanteric fractures and in unstable fractures reduction loss was significantly lower in PFN group. We observed total duration of surgery was significantly lower in PFN group. Conclusions: We concluded that PFN may be the better fixation device for most unstable inter-trochanteric fractures.